2001
DOI: 10.1016/s0014-5793(01)02707-7
|View full text |Cite
|
Sign up to set email alerts
|

Semliki Forest virus vectors: efficient vehicles for in vitro and in vivo gene delivery

Abstract: Rapidly generated high-titer Semliki Forest virus (SFV) vectors can infect numerous mammalian cell lines and primary cell cultures, and result in high levels of transgene expression. SFV-based expression of transmembrane receptors has been characterized by specific ligand-binding activity and functional responses. Adaptation of the SFV technology for mammalian suspension cultures has allowed the production of hundreds of milligrams of recombinant receptor for purification and structural studies. The same SFV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
7

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 29 publications
(41 reference statements)
1
46
0
7
Order By: Relevance
“…To efficiently express the recombinant 5-HT 2A receptor constructs in cultured neurons, we resorted to the Semliki Forest virus (SFV) expression system (Lundstrom et al, 2001;Ehrengruber, 2002), as we found the calcium phosphate technique to be much less efficient in our hands than the SFV system. We thus examined whether the viral expression system interfered with the polarized distribution of one of the subcellular markers that would be used in subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently express the recombinant 5-HT 2A receptor constructs in cultured neurons, we resorted to the Semliki Forest virus (SFV) expression system (Lundstrom et al, 2001;Ehrengruber, 2002), as we found the calcium phosphate technique to be much less efficient in our hands than the SFV system. We thus examined whether the viral expression system interfered with the polarized distribution of one of the subcellular markers that would be used in subsequent studies.…”
Section: Resultsmentioning
confidence: 99%
“…The SFV system has two additional advantages: (1) the viral genome replicates in the cytoplasm, thus obviating potential difficulties encountered with nuclear expression systems (e.g. mRNA splicing, capping and transport, and limitations in transcription factors); (2) SFV, despite its high efficiency of replication in neurons, induces cytotoxicity only after prolonged periods of infection (Lundstrom et al, 2001;Ehrengruber, 2002). The SFV expression system has thus enabled us to (EC 50 ) and relative agonist efficacy (normalized E max ) were determined from phosphoinositide hydrolysis assay as described previously (Gray et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, to obtain high yields of integral transmembrane proteins in their native form has 8 Large-scale production of recombinant receptors has also been established for SFV-infected mammalian suspension cell cultures in bioreactors and spinner flasks. 9 This approach has been successful in producing up to 10 mg receptor protein per liter culture for structural biology applications.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Many investigations have used viral vectors such as retro, adeno, adeno-associated, or alphavirus vectors. Alphavirus vectors demonstrate high-level expression of heterologous proteins in a broad host range of cells [1][2][3][4][5] and have been shown to induce apoptosis in infected cells. 6,7 Semliki Forest virus (SFV), an alphavirus, is an enveloped positive-sense RNA virus of the family Togaviridae; it has been developed into a transient RNA-based suicidal expression vector system.…”
Section: Introductionmentioning
confidence: 99%